The 86 percent solution : how to succeed in the biggest market opportunity of the next 50 years - 347000 Mahajan, Vijay; Banga, Kamini; Gunther, Robert E., 1960- (Upper Saddle River, NJ : Wharton School Publishing, 2006)
28